The validity of Marshall-Lerner condition in Turkey: A cointegration approach - Hakan TÜRKAY (Theoretical and Applied Economics, 2014)

(untitled)
In recent years, it is discussed that the currency adjustments (devaluations) may frequently have impact on current account deficit associated with the increase in current account deficit. The impact of devaluation on balance of trade depends on the effectiveness of Marshall-Lerner condition. In this study, the validity of Marshall-Lerner condition in Turkey was investigated. According to the results of Johansen cointegration test and error correction model which were obtained by using annual data of 1980-2012 period; some findings were obtained about the validity of Marshall-Lerner condition in the long run.